Postharvest mechanical damage affects fruit quality of 'Montenegrina' and 'Rainha' tangerines - Scherrer Montero, Cândida Raquel; Schwarz, Lígia Loss; Santos, Liege Cunha dos; Andreazza, Cristiane Salete; Kechinski, Carolina Pereira; Bender, Renar João (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the visual and chemical quality of tangerines after mechanical damage by impacts. The tangerine cultivars Montenegrina and Rainha were submitted to different degrees of impact and evaluated for decay and oleocellosis, loss of fresh weight, total soluble solids, total titratable acidity and ascorbic acid degradation, as well as for epicarp color changes. Experiments with three replicates and experimental units of six fruit for each cultivar were done in a completely randomized design. Impact produced qualitative internal and minor external changes on tangerines. The main modifications produced by impact on the fruit were losses of citric acid and soluble solids, which increased the solid:acid ratio, and losses of ascorbic acid. 'Montenegrina' tangerines are more susceptible to internal quality damage than 'Rainha'.